Analysis and Reconstruction of Student Worksheets on the Practicum of Catalase Enzyme, with The Tools and Materials Alternative - Shopiah Dhuha Siregar; Zhafira Zhafira; Alfyn Abdan Nurahman; Bambang Supriatno; Amprasto Amprasto (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Practicum is a process to gain meaningful learning experience through hands-on and hands-on activities. Factors that cause constraints in biology practicum include incomplete tools, unavailable materials, and unavailability of practicum guides. The practicum guides circulating in schools also have various problems. Therefore, it is necessary to reconstruct the practicum guide and the existence of tools and materials that can be an alternative or solution that can overcome problems in the practicum of catalase enzyme. This research uses a qualitative descriptive method with the ANCORB flow (Analysis-Test-Reconstruction-Test). The samples used were five pieces of catalase enzyme practicum guides (LKS) from various sources with sampling techniques in purposive sampling. The analysis showed that the average LKS of catalase enzyme had a fairly good score but still needed LKS reconstruction that could measure the work of catalase enzyme quantitatively accompanied by alternative tools and materials in catalase enzyme practicum. The alternative tools that can be used are tools assembled using a syringe and a three-way stopcock. At the same time, alternative materials that can be used are water with acidic and alkaline pH, lime, lime water and clothes bleach as a substitute for hydrogen peroxide